2018
DOI: 10.1177/1933719117704906
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Abnormal DNA Methylation of Imprinted Loci on Human Spontaneous Abortion

Abstract: Currently, there is a growing concern regarding the safety of assisted reproductive technology (ART) due to increased risk of spontaneous abortion (SA) and imprinting disorders in ART-conceived offspring. Early investigations suggested that aberrant genetic imprinting may be related to pregnancy loss; however, few studies have used human tissue specimens. Here the DNA methylation patterns of 3 imprinted genes, including maternally inherited GRB10 and the paternally inherited IGF2 and PEG3 genes, were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…There are also links to imprinting disorders [24], with Bincreased prevalence of imprinting defects in patients with Angelman syndrome born to subfertile couples^suggesting a common cause for both [25]. Doornbos et al [26] felt that increases in such disorders with assisted reproduction Bcan fully be explained by the increased fertility problems of the parents.^An imprinted gene polymorphism related to spontaneous abortions with assisted reproduction [27] supports other imprinting effects.…”
Section: Nonstructural Correlationsmentioning
confidence: 99%
“…There are also links to imprinting disorders [24], with Bincreased prevalence of imprinting defects in patients with Angelman syndrome born to subfertile couples^suggesting a common cause for both [25]. Doornbos et al [26] felt that increases in such disorders with assisted reproduction Bcan fully be explained by the increased fertility problems of the parents.^An imprinted gene polymorphism related to spontaneous abortions with assisted reproduction [27] supports other imprinting effects.…”
Section: Nonstructural Correlationsmentioning
confidence: 99%
“…During embryonic development, H19 is highly expressed; however, after birth, the expression of H19 is decreased (15). Most studies investigating H19 have focused on its role in carcinogenesis, including tumor growth and metastasis (16,17), and although several studies have analyzed the expression and methylation status of H19 in SA (18,19), whether H19 regulates apoptosis and ferroptosis in SA is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal GRB10 knockout results in embryonic overgrowth, and the change of ICR of GRB10 gene results in obvious dysplasia [20,21]. Previous studies have found an increase methylation of GRB10 in fetal samples of spontaneous abortion [22]. It has been found that the Ddc gene in mice, involved in the development of trabecular cardiomyocytes of the embryonic and neonatal heart, displays tight conserved linkage with the methylated GRB10 gene [23].…”
Section: Discussionmentioning
confidence: 99%